Exploring And Understanding The Use Of Mobile E-Book Among Mathematics Postgraduate Students - Letchumanan, Malathi (2017)
This study aimed to explore and understand the mathematics postgraduate students‟ experience with mobile e-book. In particular this study presents appreciation of meaning and experience of mathematics postgraduate students in using the mobile e-book for their research activities.This study was guided by five research questions: (a) how do the mathematics postgraduate students use the mobile e-book?; (b) what are their main purposes of using the mobile e-book?; (c) what factors and how far these factors promote and hinder the use of the mobile e-book for learning activities; (d) how does the adoption of the mobile e-book affect the way the mathematics postgraduate students learn?; and (e) What are the information needed to develop guidelines to design future mobile e-book for the designers and academicians?